Coram Populo—In the Presence of People: The Effect of Others in Virtual Worlds. Issue 3 (13th February 2013) - Goel, Lakshmi; Prokopec, Sonja; Junglas, Iris
Abstract 3D virtual worlds (VWs) enable perception of others' presence and actions. However, it is unclear how this influences behaviors in group tasks. We study the influence of 'perceived colocation' and 'perceived coaction', on cognitive absorption, which in turn predicts participative behaviors. Perceived colocation and coaction are central to social facilitation effects, tested primarily in face‐to‐face settings. We use distraction‐conflict theory to explain how these may occur in VWs. Results from a quasi‐experiment in Second Life support our hypotheses. We demonstrate the influence of perceived colocation and coaction and extend the applicability of social facilitation effects by incorporating the concept of cognitive absorption in VWs. We conclude with suggestions for the use of VWs for decision‐making tasks.